The role of lipids in ependymal development and the modulation of adult neural stem cell function during aging and disease. (April 2021) - Harkins, Danyon; Cooper, Helen M.; Piper, Michael
Abstract: Within the adult mammalian central nervous system, the ventricular-subventricular zone (V-SVZ) lining the lateral ventricles houses neural stem cells (NSCs) that continue to produce neurons throughout life. Developmentally, the V-SVZ neurogenic niche arises during corticogenesis following the terminal differentiation of telencephalic radial glial cells (RGCs) into either adult neural stem cells (aNSCs) or ependymal cells. In mice, these two cellular populations form rosettes during the late embryonic and early postnatal period, with ependymal cells surrounding aNSCs. These aNSCs and ependymal cells serve a number of key purposes, including the generation of neurons throughout life (aNSCs), and acting as a barrier between the CSF and the parenchyma and promoting CSF bulk flow (ependymal cells). Interestingly, the development of this neurogenic niche, as well as its ongoing function, has been shown to be reliant on different aspects of lipid biology. In this review we discuss the developmental origins of the rodent V-SVZ neurogenic niche, and highlight research which has implicated a role for lipids in the physiology of this part of the brain. We also discuss the role of lipids in the maintenance of the V-SVZ niche, and discuss new research which has suggested that alterations to lipid biology could contribute to ependymal cell dysfunction in aging and disease.